'Marry - stitch - die - or do worse'?: female self-employment and small business proprietorship in London c.1740 - 1880. - Kay, A; Alison C Kay (2002)
'Marry - Stitch - Die - or Do Worse' ran a Times newspaper leader in 1857. Yet a significant proportion of the adult female population at this time were surviving without a husband, particularly in London. This thesis focuses on the activities of such women who never married, were deserted or became widowed. Sometimes labelled 'redundant', 'distressed' or 'failed' by their contemporaries, they were frequently unsupported. In the face of substantial barriers to paid employment, this thesis argues that self-employment and small business proprietorship was often a viable option. The evidence presented suggests a somewhat different picture to that often generalised for all middle and upper class women in the nineteenth century - that of retreat into the private sphere of home to become the ‘angel in the house’. A wide variety of sources have been drawn upon to examine women's use of small business proprietorship as a strategy in nineteenth century London, including published diaries, trade cards, opinion pieces, trade directories and insurance records. In addition, it is argued that it is only by following the female proprietor home that we can begin to understand the role of proprietorship in women's work-life strategies. Record linkage has been used to obtain more detailed and consistent information on the families and household's of female proprietors than that available from trade directories or newspaper advertisements. Common stereotypes of women in business in this period relating to age, marital status and so on have been assessed in the light of this evidence. This research has revealed that these stereotypes have some truth in their application to women engaged in the production and typically 'male' trades but that such trades represent only a small fraction of the experience and activities of female proprietors.